2021
DOI: 10.1155/2021/5576596
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble ST2 Correlated with Symptom Severity and Clinical Response of Sublingual Immunotherapy for House Dust Mite-Induced Allergic Rhinitis Patients

Abstract: Background. Suppressor of tumorigenicity 2 (ST2) is a key biomarker in inflammation and cardiovascular diseases, but limited data is available on its role in allergic rhinitis (AR). Objective. The aim of this study is to explore the role of serum soluble ST2 (sST2) in evaluating disease severity and predicting the efficacy of sublingual immunotherapy (SLIT) in house dust mite- (HDM-) induced AR patients. Methods. Eighty healthy controls (HC group) and 160 HDM-induced AR patients, including 40 mild patients (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…Fasting blood (5 mL) was collected from each participant before the onset of SLIT, and processed and stored as described previously. 13 A human cytokine standard 31-Plex assay kit (Bio-Rad) was utilized to detect 31 cytokines — BAFF, CCL2, CCL3, CCL4, CCL7, CCL11, CXCL9, CXCL10, CXCL12, GM-CSF, IFNγ, IL1α, IL1β, IL2, IL2Rα, IL4, IL5, IL6, IL7, IL8, IL9, IL10, IL13, IL15, IL16, IL17, IL33, M-CSF, MIF, TNFα, and TNFβ — based on the Luminex 200 system, and data interpretation was conducted as previously described. 19 All samples were diluted at 1:3 with sample diluent, and data from the 31-Plex assays were transferred to an Excel spreadsheet for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fasting blood (5 mL) was collected from each participant before the onset of SLIT, and processed and stored as described previously. 13 A human cytokine standard 31-Plex assay kit (Bio-Rad) was utilized to detect 31 cytokines — BAFF, CCL2, CCL3, CCL4, CCL7, CCL11, CXCL9, CXCL10, CXCL12, GM-CSF, IFNγ, IL1α, IL1β, IL2, IL2Rα, IL4, IL5, IL6, IL7, IL8, IL9, IL10, IL13, IL15, IL16, IL17, IL33, M-CSF, MIF, TNFα, and TNFβ — based on the Luminex 200 system, and data interpretation was conducted as previously described. 19 All samples were diluted at 1:3 with sample diluent, and data from the 31-Plex assays were transferred to an Excel spreadsheet for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…During the SLIT, compliance education and follow-up were performed, medication score and total nasal symptom score (TNSS) evaluated via WeChat in the previous week and recorded weekly, and symptom and medication score (SMS) calculated as (TNSS + MS)/7, as previously described. 13 At 1-year follow-up, early efficacy of SLIT was evaluated based on change in SMS: patients who attained a 30% reduction in SMS from baseline were defined as responders and the rest nonresponders as per our previous study. 13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior publications demonstrated that AR was a heterogeneous clinical disease with a broad spectrum of severity, and limited indicators or biomarkers have been presented to monitor the disease progression and disease severity [ 5 ]. Evaluating disease severity utilizing biomarkers contributed to understand the underlying mechanisms of AR and monitor the therapeutic effect [ 6 , 7 ]. Therefore, exploring an accurate and reliable biomarker to assess AR severity is essential.…”
Section: Introductionmentioning
confidence: 99%